Interactive Health Education: Quartet Card Game for Thalassemia Awareness - Yuanita Yuanita; Priyanto; Gipta Galih Widodo (ScieClouds Publishing, 2026)
Thalassemia remains a preventable inherited blood disorder with major clinical, social, and economic consequences, particularly in countries with high carrier prevalence such as Indonesia. University students represent a strategic population for premarital prevention because they are approaching reproductive age and may soon make decisions related to marriage, family planning, and genetic screening. This study aimed to evaluate the effectiveness of a Quartet Card Game as an interactive educational medium for improving knowledge, attitudes, and behavioral intention toward thalassemia screening among students of YPIB Majalengka University. A quantitative experimental study with a pre-test and post-test control group design was conducted. Participants were randomly assigned to an intervention group that received education using the Quartet Card Game and a control group that received conventional lecture-based education. Data were collected using a structured questionnaire measuring thalassemia knowledge, attitudes toward screening, and intention to participate in screening. Inferential analysis showed that the intervention group experienced greater improvement in all outcome variables than the control group. The Quartet Card Game significantly increased students’ knowledge of thalassemia strengthened positive attitudes toward premarital screening and encouraged stronger intention to participate in screening programs. These findings indicate that game-based education can support health promotion by transforming genetic information into active, peer-based, and behavior-oriented learning. The study contributes to thalassemia prevention research by extending game-based educational intervention to university students and by examining cognitive and behavioral outcomes within the Health Belief Model framework. Future studies should include multicenter samples, longer follow-up, and actual screening uptake as an outcome.